Lateral Flow Immunoassay - Raphael C. Wong, Harley Y. Tse (2009)
In this book, we have compiled the essence of the current state of the art of this technology and addressed what can be expected in the future. After an introduction on the evolution of the technology,some market information is provided.They are followed by discussions on the various materials, biological and chemical components involved in making the test. A chapter on manufacturing equipment and process completes the production section. Later chapters concentrate on the common issues encountered by the users or developers of the technology. Discussions are made on the design of handheld readers, the causes of false results and some way to reduce them, and the regulatory aspects in the development and marketing of lateral flow immunoassay devices.